2021
DOI: 10.1021/acs.inorgchem.0c03484
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Vanadium(III) Chalcogenidostannates Incorporating [V(tepa)]3+ Complexes as Bridging Groups

Abstract: Two new one-dimensional (1D) vanadium­(III) chalcogenidostannates, [H2tepa]0.5n [VIII(tepa)­(μ-Sn2Q6)] n [Q = S (1), Se (2); tepa = tetraethylenepentamine], were achieved by solvothermal methods, which offer the first examples of organic hybrid polymeric chalcogenidostannates incorporating [V­(tepa)]3+ complexes as bridging groups. Both 1 and 2 feature the 1D sinusoidal chains of [VIII(tepa)­(μ-Sn2Q6)] n containing two types of novel bridging modes of the [μ-Sn2Q6]4– anion. Their magnetic, photocurrent respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…17 Magnetic behavior, high-field EPR investigations, and theoretical studies concluded to the absence of first-order spin-orbit coupling due to degeneracy lifting of the two lower energy levels, and converged on anisotropy parameters D in the range of 3.9-4.5 cm À1 , and negligibly small E. For two complexes, [V III (tepa)(m-Sn 2 Q 6 )] n (tepa stands for tetraethylenepentamine, Q = S or Se), featuring an open N5pentadentate ligand and either S or Se atoms in the apical positions, magnetic behavior has been reported but no information on magnetic anisotropy has been provided. 18 Significantly larger ZFS effects have been found for second and third row metal ions. A 4d complex with Mo IV , [Mo(L1 Ph )Cl 2 ], was found to undergo a rapid decrease of its magnetic moment below 50 K attributed to thermal depopulations of the excited M S = AE1 levels resulting from ZFS of the S = 1 triplet state.…”
Section: I1 D 1 Ions (V Iv )mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Magnetic behavior, high-field EPR investigations, and theoretical studies concluded to the absence of first-order spin-orbit coupling due to degeneracy lifting of the two lower energy levels, and converged on anisotropy parameters D in the range of 3.9-4.5 cm À1 , and negligibly small E. For two complexes, [V III (tepa)(m-Sn 2 Q 6 )] n (tepa stands for tetraethylenepentamine, Q = S or Se), featuring an open N5pentadentate ligand and either S or Se atoms in the apical positions, magnetic behavior has been reported but no information on magnetic anisotropy has been provided. 18 Significantly larger ZFS effects have been found for second and third row metal ions. A 4d complex with Mo IV , [Mo(L1 Ph )Cl 2 ], was found to undergo a rapid decrease of its magnetic moment below 50 K attributed to thermal depopulations of the excited M S = AE1 levels resulting from ZFS of the S = 1 triplet state.…”
Section: I1 D 1 Ions (V Iv )mentioning
confidence: 99%
“…For two complexes, [V III (tepa)(μ-Sn 2 Q 6 )] n (tepa stands for tetraethylenepentamine, Q = S or Se), featuring an open N5-pentadentate ligand and either S or Se atoms in the apical positions, magnetic behavior has been reported but no information on magnetic anisotropy has been provided. 18…”
Section: Transition Metal Ions With a Pentagonal Bipyramidal Coordina...mentioning
confidence: 99%
“…The coordination environment of vanadium atoms (2I + O + 4Se) represents a distorted pentagonal bipyramid (Figure c). For vanadium cations, coordination number 7 may be found both for mononuclear vanadium complexes and a binuclear complex …”
Section: Results and Discussionmentioning
confidence: 99%